Edukasi Cerdas Finansial Melalui Literasi Keuangan, Perencanaan dan Pengelolaan Keuangan Langkah Bijak Menuju Kebebasan Finansial - Susilowati, Heni; Hargyatni, Titin; Sulistyowati, Pemilia; Widyaningsih, Dewi; Kusumaningsih, Dhevi Dadi; Kustami, Endang; Maulana, Putri Anindya (Universitas Pahlawan Tuanku Tambusai, 2025)
Individual or family finances are a crucial aspect of daily life that will affect family welfare. Financial literacy, good financial planning and management enable individuals to make wise financial decisions. The aim of this service activity is to provide financial intelligence education through financial literacy, financial planning and management, wise steps towards financial freedom. Financially intelligent education was provided to residents of Gladagsari Boyolali Village accompanied by 22 literacy activists. The method for carrying out service activities is by giving lectures in the form of education about financial literacy which consists of financial knowledge and financial behavior as well as personal/family financial planning which consists of preparing budgets, planning and managing routine needs, savings, debt and investments. As a result of this Community Service activity, participants can better understand financial literacy and can implement ways to plan and manage family finances.